Water soluble cationic dextran derivatives containing poly(amidoamine) dendrons for efficient gene delivery. (5th June 2015) - Mai, Kaijin; Zhang, Shanshan; Liang, Bing; Gao, Cong; Du, Wenjun; Zhang, Li-Ming
Highlights: New dextran derivative containing poly(amidoamine) dendrons was synthesized and characterized. Such a dextran derivative could condense plasmid DNA into nanocomplexes. Such a dextran derivative exhibited much lower cytotoxicity than commercial polyethylenimine. Such a dextran derivative was found to have good gene delivery capability. Abstract: To develop new dextran derivatives for efficient gene delivery, the conjugation of poly(amidoamine) dendrons onto biocompatible dextran was carried out by a Cu(I)-catalyzed azide-alkyne cycloaddition, as confirmed by FTIR and 1 H NMR analyses. For resultant dextran conjugates with various generations of poly(amidoamine) dendrons, their buffering capacity and in vitro cytotoxicity were evaluated by acid–base titration and MTT tests, respectively. In particular, their physicochemical characteristics for the complexation with plasmid DNA were investigated by the combined analyses from agarose gel electrophoresis, zeta potential, particle size, transmission electron microscopy and fluorescence emission spectra. Moreover, their complexes with plasmid DNA were studied with respect to their transfection efficiency in human embryonic kidney (HEK293) cell lines. In the case of a higher generation of poly(amidoamine) dendrons, such a dextran conjugate was found to have much lower cytotoxicity and better gene delivery capability when compared to branched polyethylenimine (bPEI, 25 kDa), a commonly used gene vector.